2017
DOI: 10.1007/s00216-017-0379-6
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of an ultrasound-assisted derivatization for GC/MS analysis of oxygenated organic species in atmospheric aerosol

Abstract: A novel ultrasound-assisted derivatization followed by GC/MS analysis was developed for the quantification of oxygenated organic species in ambient aerosol. Derivatization parameters mostly influencing the analytical response were investigated, i.e., solvent type, reagent concentration, and reaction duration. Response surface methodology was used to design experiments and a quadratic model was utilized to predict the variables and establish the optimal conditions. The study was performed on standard solutions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…In particular, the use of US in sample preparation should be promoted (Castro & Delgado‐Povedano, ), and the reaction process can be shortened with US (Fiamegos, Nanos, & Stalikas, ). Pietrogrande et al optimized mild conditions with US‐assisted derivatization at room temperature for 45 min (Pietrogrande et al, ). Prata et al found that the derivatization time can be reduced with US for detecting THCOOH in urine samples (Prata et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the use of US in sample preparation should be promoted (Castro & Delgado‐Povedano, ), and the reaction process can be shortened with US (Fiamegos, Nanos, & Stalikas, ). Pietrogrande et al optimized mild conditions with US‐assisted derivatization at room temperature for 45 min (Pietrogrande et al, ). Prata et al found that the derivatization time can be reduced with US for detecting THCOOH in urine samples (Prata et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…The total ratio of OA derivatives was higher at 40 min than at 20, 30, or 50 min. Pietrogrande et al have reported that the derivatization time for oxygenated organic species in atmospheric aerosol can be shortened from 70 min, as required by the conventional heating method, to 45 min with US assistance (Pietrogrande et al, ). In agreement with those findings, our results indicated the duration time could be shortened with US, and 40 min was chosen as the optimal condition for derivatization.…”
Section: Resultsmentioning
confidence: 99%
“…Ultrasonic cavitation through solvent can increase the reaction temperature and pressure and promote interactions between a substrate and the derivatization reagent, thereby enhancing the chemical reaction. Pietrogrande et al 20 used ultrasound‐assisted derivatization to shorten the derivatization time of oxyorganics in atmospheric aerosols (45 vs. 70min).…”
Section: Resultsmentioning
confidence: 99%
“…DCAs can be found as degradation markers of modern painting oils, , biodegradable plastics, and biomass burning . Also, dicarboxylic acids were known to be important components in the process of secondary organic aerosols formation , and pristine atmosphere …”
Section: Introductionmentioning
confidence: 99%